Regression of human coronary artery plaque is associated with a high ratio of (18‐hydroxy‐eicosapentaenoic acid + resolvin E1) to leukotriene B4. Issue 4 (22nd March 2021) - Welty, Francine K.; Schulte, Fabian; Alfaddagh, Abdulhamied; Elajami, Tarec K.; Bistrian, Bruce R.; Hardt, Markus
Abstract: Inflammation in arterial walls leads to coronary artery disease (CAD). We previously reported that a high omega‐3 fatty index was associated with prevention of progression of coronary atherosclerosis, a disease of chronic inflammation in the arterial wall. However, the mechanism of such benefit is unclear. The two main omega‐3 fatty acids, eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), are precursors of specialized pro‐resolving lipid mediators (SPMs)–resolvins and maresins–which actively resolve chronic inflammation. To explore whether SPMs are associated with coronary plaque progression, levels of SPMs and proinflammatory mediators (leukotriene B4 [LTB4 ] and prostaglandins) were measured using liquid chromatography‐tandem mass spectrometry in 31 statin‐treated patients with stable CAD randomized to either EPA and DHA, 3.36 g daily, or no EPA/DHA (control). Coronary plaque volume was measured by coronary computed tomographic angiography at baseline and at 30‐month follow‐up. Higher plasma levels of EPA+DHA were associated with significantly increased levels of two SPMs–resolvin E1 and maresin 1–and 18‐hydroxy‐eicosapentaenoic acid (HEPE), the precursor of resolvin E1. Those with low plasma EPA+DHA levels had a low (18‐HEPE+resolvin E1)/LTB4 ratio and significant plaque progression. Those with high plasma EPA+DHA levels had either low (18‐HEPE+resolvin E1)/LTB4 ratios with significant plaque progression or high (18‐HEPE+resolvin E1)/LTB4 ratios with significant plaque regression. These findings suggest that an imbalance between pro‐resolving and proinflammatory lipid mediators is associated with plaque progression and potentially mediates the beneficial effects of EPA and DHA in CAD patients.